The proper care of optics : cleaning, handling, storage, and shipping - Schalck, Robert (SPIE Press monograph, 2019)
If you want the best performance from your optics, they need to be properly maintained. This book describes the cleaning, handling, and storage methods used by professional technicians to keep optics in top condition. It is written for a diverse audience, from first-time optical cleaners to assembly technicians and seasoned engineers looking to expand their repertoire. In the lab or in the field, you'll find the right technique to protect your equipment from harm. Reference lists of tools, solvents, and suppliers are provided to help you find solutions quickly. This updated version includes additional pictures and tips to help readers safeguard their optics.